Nanoencapsulation of Pomegranate Extract to Increase Stability and Potential Dermatological Protection - Lucía Yepes-Molina; José A. Hernández; Micaela Carvajal (MDPI AG, 2021)
Pomegranate extract (PG-E) has been reported to exert a protective effect on the skin due to its antioxidant activity. Ingredients rich in phenolic compounds are unstable in extract solutions, and, therefore, the use of a suitable nanosystem to encapsulate this type of extract could be necessary in different biotechnological applications. Thus, we investigated the capacity of Brassica oleracea L. (cauliflower) inflorescence vesicles (CI-vesicles) to encapsulate PG-E and determined the stability and the antioxidant capacity of the system over time. In addition, the protective effect against UV radiation and heavy metals in HaCaT cells was also tested. The CI-vesicles had an entrapment efficiency of around 50%, and accelerated stability tests did not show significant changes in the parameters tested. The results for the HaCaT cells showed the non-cytotoxicity of the CI-vesicles containing PG-E and their protection against heavy metals (lead acetate and mercuric chloride) and UV-B radiation through a reduction of oxidative stress. The reduction of the percentage of deleted mtDNA (mtDNA4977, "common deletion") in UV-treated HaCaT cells due to the presence of CI-vesicles containing PG-E indicated the mechanism of protection. Therefore, the effects of CI-vesicles loaded with PG-E against oxidative stress support their utilization as natural cosmeceuticals to protect skin health against external damage from environmental pollution and UV radiation.